Novel conserved domains in proteins with predicted roles in eukaryotic cell-cycle regulation, decapping and RNA stability - Anantharaman, Vivek (BioMed Central, 2004)
BACKGROUND: The emergence of eukaryotes was characterized by the expansion and diversification of several ancient RNA-binding domains and the apparent de novo innovation of new RNA-binding domains. The identification of these RNA-binding domains may throw light on the emergence of eukaryote-specific systems of RNA metabolism. RESULTS: Using sensitive sequence profile searches, homology-based fold recognition and sequence-structure superpositions, we identified novel, divergent versions of the Sm domain in the Scd6p family of proteins. This family of Sm-related domains shares certain features of conventional Sm domains, which are required for binding RNA, in addition to possessing some unique conserved features. We also show that these proteins contain a second previously uncharacterized C-terminal domain, termed the FDF domain (after a conserved sequence motif in this domain). The FDF domain is also found in the fungal Dcp3p-like and the animal FLJ22128-like proteins, where it fused to a C-terminal domain of the YjeF-N domain family. In addition to the FDF domains, the FLJ22128-like proteins contain yet another divergent version of the Sm domain at their extreme N-terminus. We show that the YjeF-N domains represent a novel version of the Rossmann fold that has acquired a set of catalytic residues and structural features that distinguish them from the conventional dehydrogenases. CONCLUSIONS: Several lines of contextual information suggest that the Scd6p family and the Dcp3p-like proteins are conserved components of the eukaryotic RNA metabolism system. We propose that the novel domains reported here, namely the divergent versions of the Sm domain and the FDF domain may mediate specific RNA-protein and protein-protein interactions in cytoplasmic ribonucleoprotein complexes. More specifically, the protein complexes containing Sm-like domains of the Scd6p family are predicted to regulate the stability of mRNA encoding proteins involved in cell cycle progression and vesicular assembly. The Dcp3p and FLJ22128 proteins may localize to the cytoplasmic processing bodies and possibly catalyze a specific processing step in the decapping pathway. The explosive diversification of Sm domains appears to have played a role in the emergence of several uniquely eukaryotic ribonucleoprotein complexes, including those involved in decapping and mRNA stability.